(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, the following statememt of Fermat’s Last Theorem is proved. If x; y; z are positive integers, _ is an odd prime and z_ = x_ + y_; then x; y; z are all even. Also, in this paper, is proved Beal’s conjecture; the equation z_ = x_ + y_ has no solution in relatively prime positive integers x; y; z; with _; _; _ primes at least 3: